LncRNA CRNDE promotes hepatocellular carcinoma cell proliferation, invasion, and migration through regulating miR‐203/ BCAT1 axis. Issue 5 (19th September 2018) - Ji, Degang; Jiang, Chengwei; Zhang, Lirong; Liang, Na; Jiang, Tiechao; Yang, Bin; Liang, Haiying
Abstract: Objective: To investigate the impact of long noncodingRNA (lncRNA) colorectal neoplasia differentially expressed (CRNDE) on hepatocellular cancer (HCC) cell propagation, invasion, and migration by mediating miR‐203/ BCAT1 axis. Methods: Microarray analysis was based on 25 pairs of HCC cancerous tissues and adjacent tissues. The expression levels of CRNDE, miR‐203, and BCAT1 in HCC tissues were analyzed by quantitative real‐time polymerase chain reaction (qRT‐PCR). The liver cell line L‐02 and HCC cell lines HepG2 and Huh‐7 were utilized to assess the regulatory eﬀects of CRNDE and miR‐203 on HCC progression in vitro. Western blot was used to qualify BCAT1 protein expression level. Cell proliferation and apoptosis were evaluated using CCK‐8 and flow cytometry analysis, whereas cell invasion and migration assay were performed by the Transwell assay. The relationship among CRNDE, miR‐203, and BCAT1 was validated by dual luciferase assay. Tumor Xenograft study was established to verify the pathological effect of CRNDE on HCC development in vivo. Results: The expression levels of the CRNDE and BCAT1 were upregulated in HCC tissues and cells, whereas miR‐203 was downregulated in HCC. Knockdown of CRNDE or miR‐203 overexpression would inhibit HCC cell propagation and metastasis, and induced cell apoptosis. Moreover, miR‐203 was negatively correlated with CRNDE, the same as miR‐203 with BCAT1 . Dual luciferase assay showed that miR‐203 was an inhibitory target of CRNDE, and BCAT1 was directly targeted by miR‐203 as well. Conclusion: LncRNA CRNDE could enhance HCC tumorgenesis by sponging miR‐203 and mediating BCAT1 . LncRNA CRNDE might facilitate HCC cell propagation, invasiveness, and migration through regulating miR‐203/ BCAT1 axis. Abstract : Long noncodingRNA colorectal neoplasia differentially expressed (CRNDE) could facilitate hepatocellular cancer (HCC) cell propagation, invasiveness, and migration through regulating miR‐203/ BCAT1 axis. This finding not only disclosed the regulatory mechanism of CRNDE/miR‐203/BCAT1 network in HCC, but also provided novel biomarkers and therapeutic targets for the clinical diagnosis and treatment of HCC.